The Little Green Data Book 2002 - World Bank (Washington, DC, 2013)
The Little Green Data Book represents a succinct collection of information from the World Development Indicators 2002, and its accompanying CD-ROM. The data compiled in this issue corresponds to the period between 1997 and 2000, unless otherwise noted, for the headings of agriculture, forests, biodiversity, energy, emissions and pollution, water and sanitation, and "greener" national accounts aggregates - 2000, with key indicators of the environment, and its relationship to people for more than 200 countries. Regional data include only low- and middle-income economies, and, aggregates for regions, and income groups are shown only if data are available for 66 percent of the economies in that group. Countries included have populations of more than 30,000, or are World Bank members.